Negative affectivity in university students and its relationship with academic performance and professional outlook after COVID-19 - Bruna de Oliveira Alves; Bárbara Guimarães Lourenço; Bianca Bacelar Assis Araújo; Luana Vieira Toledo; Rafael Lopes Chaves; Érika de Cássia Lopes Chaves; Tânia Couto Machado Chianca; Caroline de Castro Moura (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to evaluate the prevalence of negative affectivity in university students in the post-COVID-19 pandemic context and its relationship with academic performance and professional outlook. Methods: a cross-sectional study was conducted with undergraduate students from a public university in Minas Gerais between September 2022 and September 2023. Data were collected using a sociodemographic and psychosocial characterization questionnaire and the Depression, Anxiety, and Stress Scale 21. The relationships between negative affectivity, academic performance, and professional outlook were verified using the Kruskal-Wallis test, with a significance level of 5%. Results: a total of 585 students participated in the study. A high prevalence of depression, anxiety, and stress was found among university students in the post-COVID-19 context, with a notable severity of anxiety. A negative association was detected between the investigated negative affectivity, academic performance, and professional outlook. Conclusions: the results indicate an emotional vulnerability in university students, with a relationship between negative affectivity and a decline in academic performance and professional outlook.